1999
DOI: 10.1046/j.1365-2826.1999.00408.x
|View full text |Cite
|
Sign up to set email alerts
|

GHRP‐6‐Induced Changes in Electrical Activity of Single Cells in the Arcuate, Ventromedial and periventricular nucleusriventricular Nuclei of a Hypothalamic Slice Preparation in Vitro

Abstract: Previously, we demonstrated that systemic injection of the growth hormone secretagogue, growth hormone-releasing peptide (GHRP)-6, selectively activated cells in the hypothalamic arcuate nucleus, as reflected by increased electrical activity and induction of the immediate early gene c-fos. The growth hormone secretagogue receptor distribution is not confined to the arcuate nucleus, suggesting that additional sites of action may exist. In the present study we characterized the electrophysiological responses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…On the other hand, the lack of expression of the GHS-R in the lateral hypothalamus (LHA) (17), where a large number of orexigenic neurons are located (22,23), suggested that this hypothalamic nucleus was unlikely to be a target of the effects of ghrelin on food intake. However, some of the biological effects of ghrelin might be mediated by as yet unknown receptors, different from the only one cloned until now (24,25). In keeping with this possibility, it was found that ghrelin administration leads to increased c-Fos expression in neurons of the LHA (26).…”
mentioning
confidence: 92%
“…On the other hand, the lack of expression of the GHS-R in the lateral hypothalamus (LHA) (17), where a large number of orexigenic neurons are located (22,23), suggested that this hypothalamic nucleus was unlikely to be a target of the effects of ghrelin on food intake. However, some of the biological effects of ghrelin might be mediated by as yet unknown receptors, different from the only one cloned until now (24,25). In keeping with this possibility, it was found that ghrelin administration leads to increased c-Fos expression in neurons of the LHA (26).…”
mentioning
confidence: 92%
“…Ghrelin stimulates food intake after both central and peripheral administration [25, 26]. As demonstrated by recent studies, ghrelin [27, 28]and artificial growth hormone secretagogues [29, 30], which also bind to the GHS-R, directly activate leptin-responsive cells of the ArcM, where NPY-expressing neurons are regionally clustered [20]. As an indirect effect, ghrelin presynaptically inhibits neurons in the lateral Arc (ArcL) [28], where POMC-expressing neurons predominate [20].…”
Section: Introductionmentioning
confidence: 99%
“…Many ARC GHRH neurons have GHS-R [31] and GHS stimulation increased both ARC c-fos expression [32,33] and ARC electrical activity in vivo [34] and in vitro [35]. Pretreatment of rats with GHRH antiserum [36] or administration of a GHRH-R antagonist to humans [37] blocked most of the GH response to GHRP-6.…”
mentioning
confidence: 99%